Formonix Hi-Tech / Nurul Izzah Amuary … [et al.] - Amuary, Nurul Izzah; Zulkefli, Qisthina Shuhada; Aznam, Adilah Hanim; Mohd Fakhrurrozi, Nuranis Syahirah; Hanafi, Nur Amalia Filza (2022)
Formonix Hi-Tech is a product oriented business which sells shoes dryer. Our motto is “Expert care with advance life”. The mission for our business are to make it easier for athletes to dry their shoes. It is because we identified that athletes have problem of wet and smelly shoes after their practice. We also discovered that Orang Asli students aged between 7-18 years old went to school barefoot or they did not come to school when heavy rain poured. It is because most parents from Orang Asli village could not afford to buy their kids extra shoes due to poverty. So, we want to help Orang Asli earn money and skills by hired them to involved in making our shoes dryer. Therefore, Formonix Hi-Tech invented Shoes Dryer with a new technology that includes fragrance. Our vision is to become one of the best and well-known shoes dryer on the market. Formonix Hi-Tech is located at Kawasan Perindustrian Tapah, 35400 Road, Perak. We choose this location because we have considered the distance between Orang Asli Village in Tapah with the company building at Tapah Road. Hence, it is not difficult for them to go to work as the distance is not far. Formonix Hi-Tech operates from Monday to Friday and our operating hours are from 8 am to 5 pm. The business is a partnership between 5 members which are Nurul Izzah Binti Amuary as general manager, Nur Amalia Filza Binti Hanafi as financial manager, Adilah Hanim Binti Aznam as operational manager, Nuranis Syahirah Binti Mohd Fakhrurrozi as marketing manager and Qisthina Shuhada Binti Zulkefli as organizational manager. The total amount of capital the partners invest in this business in RM 100,000. All the partners contribute equally for RM 20,000 for the capital. All partners will have equal control unless otherwise specified in a partnership agreement.